2016
DOI: 10.1155/2016/2164761
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Diverse Bacteria from Aquaculture in Borneo

Abstract: The administration of antimicrobials in aquaculture provides a selective pressure creating a reservoir of multiple resistant bacteria in the cultured fish and shrimps as well as the aquaculture environment. The objective of this study was to determine the extent of antibiotic resistance in aquaculture products and aquaculture's surrounding environment in Sarawak, Malaysian Borneo. Ninety-four identified bacterial isolates constituted of 17 genera were isolated from sediment, water, and cultured organisms (fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 23 publications
(28 reference statements)
3
34
2
Order By: Relevance
“…There is published report that had stated moderate ceftazidime resistance (24%-29%) from aquaculture farm (Resende et al, 2017) which is comparatively similar to E. coli resistance (30.9%) in our study. The percentage of chloramphenicol (21% to 53%) in our study seems too high when compared (4%) with the other previous reported studies of Korea and Malaysia (Kathleen et al, 2016;Yoo, Huh, Kim, Lee, & Do Jeong, 2003). The percentage of chloramphenicol (21% to 53%) in our study seems too high when compared (4%) with the other previous reported studies of Korea and Malaysia (Kathleen et al, 2016;Yoo, Huh, Kim, Lee, & Do Jeong, 2003).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…There is published report that had stated moderate ceftazidime resistance (24%-29%) from aquaculture farm (Resende et al, 2017) which is comparatively similar to E. coli resistance (30.9%) in our study. The percentage of chloramphenicol (21% to 53%) in our study seems too high when compared (4%) with the other previous reported studies of Korea and Malaysia (Kathleen et al, 2016;Yoo, Huh, Kim, Lee, & Do Jeong, 2003). The percentage of chloramphenicol (21% to 53%) in our study seems too high when compared (4%) with the other previous reported studies of Korea and Malaysia (Kathleen et al, 2016;Yoo, Huh, Kim, Lee, & Do Jeong, 2003).…”
Section: Discussioncontrasting
confidence: 86%
“…Along with this, others have reported approximately 10%-29% of resistance against amikacin in aquaculture environment (Resende et al, 2017). For streptomycin, similar high results were also reported by the study (85%) published in Malaysia (Kathleen et al, 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Antibiotics commonly used as treatment to control E. tarda infection (Kholil et al, 2015). However, the use of antibiotics can cause bacteria to be resistant to some antibiotics that has been used (Kadlec et al, 2011;Kathleen et al, 2016;Qiao et al, 2018). Several studies have been conducted to determine the resistance of E. tarda due to the use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The same phenomenon of spreading unknown new diseases in the regions to the native population occurred after 1492 in the Americas [1] [16] and in Europe [17]. The use of antibiotics in poultry [18], fish farming [19], and animal farming [20] contributed to and continues to contribute to antibiotic resistance and multiple antibiotic resistances, especially the spreading of MRSA. Bacteriocins and other cationic peptides/small proteins (such as lysozyme) became an antibiotic group for use for topical application and for use in the food industry [21].…”
Section: Introductionmentioning
confidence: 99%